Necrotizing external otitis: analysis of relapse risk factors in 66 patients managed during a 12 year period. (13th June 2022) - Danjou, William; Chabert, Paul; Perpoint, Thomas; Pradat, Pierre; Miailhes, Patrick; Boibieux, André; Becker, Agathe; Fuchsmann, Carine; Laurent, Frédéric; Tringali, Stephane; Roux, Sandrine; Triffault-Fillit, Claire; et al.
Abstract: Background: Necrotizing external otitis (NEO) is a severe infection of the skull base that occurs generally in the elderly and/or in diabetic recipients. There are few data in the literature about the therapeutic management of this complex bone infection. Objectives: To analyse relapses after NEO treatment completion, and to describe the clinical features of NEO. Methods: We performed a retrospective cohort study in the Lyon regional reference centre for the management of complex bone and joint infections. Consecutive cases of NEO from 1 January 2006 to 31 December 2018 were included. The primary outcome was the relapse of NEO. Variables were analysed using Cox regression survival analysis with adjusted hazard ratio (aHR) and Kaplan–Meier curve. Results: Sixty-six patients were included. Median age was 75 (IQR 69–81) years and 46 (70%) patients were diabetic. Eleven patients (17%) had temporomandibular arthritis, 10 (15%) cranial nerve paralysis, 2 (3%) cerebral thrombophlebitis, and 2 (3%) contiguous abscess. Microbiological documentation was obtained in 56 patients and revealed Pseudomonas aeruginosa in 44/56 patients (79%). Nine (14%) cases had no microbiological documentation. Antibiotic therapy was dual for 63 (95%) patients. During a median follow-up of 27 (IQR 12–40) months, 16 out of 63 (25%) patients experienced a relapse. Fungal infection was significantly associated with relapse [aHR 4.1 (95% CI 1.1–15); P =  0.03]. Conclusions: NEO is a severe bone infection, mainly (but not exclusively) caused by P. aeruginosa, which occurs in elderly and diabetic recipients. Fungal infections at baseline significantly impact the outcome.